The varied Q creatinine in multi ethnics population and impact of adopting three different estimated glomerular filtration rates based on creatinine in adult populations: a call for performance validation - Marpaung, Ferdy Royland; Purnami, Santi Wulan; Andari, Shofi; Rohman, Ali; I’tishom, Reny; Notobroto, Hari Basuki; Nugraha, Jusak; Prasetyo, Risky Vitria; Santoso, Djoko; Cavalier, Etienne; Aryati, Aryati (Frontiers in Medicine, 2025)
BackgroundThe determination of kidney function is commonly done by estimating the glomerular filtration rate (eGFR) using serum creatinine levels. Various eGFR formulas, including the recently developed European Kidney Function Consortium (EKFC) and the Chronic Kidney Disease Epidemiology Collaboration(CKD-EPI), have been adopted and are commonly utilized in clinical settings. Nevertheless, the extent of acceptance among these formulations in the multi ethnics populace is still undetermined. Thus, this study aimed to evaluate the performance of these formulations across different glomerular filtration rate categories in the adult population.MethodsThe research involved a total of 9,557 individuals (median age of 40 years and 85% being male) who underwent routine medical examinations. Enzymatic or modified Jaffe techniques were employed to measure serum creatinine levels. The CKD-EPI2009 eGFR was employed as corresponding GFR in the comparisons. The Bland–Altman method was used to determine the average discrepancies and 95% confidence intervals of eGFR between each formula. Ultimately, in order to compare the equations, Lin’s correlation coefficients were calculated for various eGFR categories.ResultsThe median creatinine level in the different island population showed variability. The CKD-EPI 2009 as well as different equations showed categorical agreement within the range of 91.42 to 92.77%. The correlations between CKD-EPI2009 and CKD-EPI 2021 and EKFC were 0.998 and 0.79, respectively (p < 0.001).ConclusionA substantial variation in creatinine and eGFR assessment were observed among different eGFR analysis for the adult population. Prospective study in various clinical contexts using measured GFR is essential to validate eGFR.